2022
DOI: 10.1093/cid/ciac581
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Clearance of Anal Human Papillomavirus Infection in 16 164 Individuals, According to Human Immunodeficiency Virus Status, Sex, and Male Sexuality: An International Pooled Analysis of 34 Longitudinal Studies

Abstract: Background Understanding the natural history of anal high-risk human papillomavirus (hrHPV) infection is key for designing anal cancer prevention programmes but has not been systematically characterised. Methods We reanalysed data from 34 studies with 16 164 individuals in six risk groups defined by HIV status, gender, and male sexuality: men who have sex with men (MSM) living with HIV (LWH) [MSMLWH], HIV-negative MSM, women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 31 publications
1
13
0
1
Order By: Relevance
“…This might be surprising given that HIV-infected subjects are more likely to harbor anal HPV and HPVrelated lesions 2,7 and display higher incidence and lower clearance rates of high-risk types compared with the HIV-uninfected counterparts. 24 However, HIV-uninfected and HIV-infected MSM of our study displayed major differences in terms of age and sexual exposure. HIV-uninfected MSM were significantly younger and displayed a higher sexual exposure (more lifetime and recent partners, more likely to have casual partners) than the HIV-infected counterparts.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…This might be surprising given that HIV-infected subjects are more likely to harbor anal HPV and HPVrelated lesions 2,7 and display higher incidence and lower clearance rates of high-risk types compared with the HIV-uninfected counterparts. 24 However, HIV-uninfected and HIV-infected MSM of our study displayed major differences in terms of age and sexual exposure. HIV-uninfected MSM were significantly younger and displayed a higher sexual exposure (more lifetime and recent partners, more likely to have casual partners) than the HIV-infected counterparts.…”
Section: Discussionmentioning
confidence: 63%
“…Interestingly, our study showed no significant differences between the two groups. This might be surprising given that HIV‐infected subjects are more likely to harbor anal HPV and HPV‐related lesions 2,7 and display higher incidence and lower clearance rates of high‐risk types compared with the HIV‐uninfected counterparts 24 . However, HIV‐uninfected and HIV‐infected MSM of our study displayed major differences in terms of age and sexual exposure.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations